Use of acoustic monitoring to estimate occupancy of the Antioquia Brushfinch (Atlapetes blancae), a critically endangered species, in San Pedro de los Milagros, Antioquia (2023)
ABSTRACT: The Antioquia Brushfinch (Atlapetes blancae) is a passerine bird from the Passerellidae family, endemic to the Santa Rosa de Osos high elevation plateau (ASRO) in the department of Antioquia-Colombia. It is threatened nationally and globally, presumably by the destruction of its habitat and small population size. The Antioquia Brushfinch was described in 2007 from three specimens collected in 1971 and was considered possibly extinct until its rediscovery in 2018. Despite the difficulty in obtaining information on its vital rates, some methodologies have recently been proposed to estimate population state variables, such as occupancy. Occupancy is a basic population state variable reflecting the probability that a sampling unit, taken at random from the study area, is occupied. In the present work, we sampled 80 sites (30 m radius circles) to monitor acoustic activity using autonomous recorders and estimated the probability of occupancy of the Antioquia Brushfinch in an area of the municipality of San Pedro de los Milagros, Antioquia. Based on our observations of habitat use by the species, we evaluated the following set of covariates for occupancy: the amount of shrubby and herbaceous vegetation, the presence of water bodies, and terrain concavity. For detection probability (the probability of recording an organism given that the site is occupied), we evaluated the time of each record as a covariate. The average occupancy and detection probability of the Antioquia Brushfinch across sampling units was 0.11 ± 0.06 SE and 0.1 ± 0.07 SE, respectively, indicating low occupancy and probability of detection. We found that areas with intermediate proportions of shrubby and herbaceous vegetation and concave terrain relief promote the occupancy of the Antioquia Brushfinch. The probability of obtaining acoustic records of this species with the set of autonomous recorders increased toward the morning hours. The information and results obtained will provide guidelines for conservation actions in the area of occupancy of the Antioquia Brushfinch.